Pembelajaran Sejarah Berbasis Media Online dalam Meningkatkan Kemampuan Literasi Digital Siswa di Era Revolusi Industri 4.0 - Tunggul Wijaya; Suryo Ediyono (Universitas Sebelas Maret, 2022)
The process of historical learning in the limited face-to-face system was done by using a blended learning model. This model requires the role of online media to help synchronous and asynchronous learning process. This study aims to analyze the role of online media as the latest form of learning in improving digital literacy skills. This type of research is descriptive qualitative with a case study approach. The research was conducted at SMA N 1 Ceper using data collection methods through interviews with 20 social studies students in grades XI and XII, document analysis, and observation. The results of this study show 1) Students' readiness to learn in an online learning environment, 2) students very often use online media as a source of independent learning materials during synchronous and asynchronous learning process, 3) students use digital media for collaboration and problem solving. Thus, online media plays an important role in increasing students' digital literacy as an important ability in the era of the industrial revolution 4.0.